2011
DOI: 10.1007/s00436-011-2277-8
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal, pediculocidal and larvicidal activity of synthesized ZnO nanoparticles using wet chemical route against blood feeding parasites

Abstract: The present study was based on assessments of the anti-parasitic activities to determine the efficacies of synthesized zinc oxide nanoparticles (ZnO NPs) prepared by wet chemical method using zinc nitrate and sodium hydroxide as precursors and soluble starch as stabilizing agent against the larvae of cattle tick Rhipicephalus (Boophilus) microplus, Canestrini (Acari: Ixodidae); head louse Pediculus humanus capitis, De Geer (Phthiraptera: Pediculidae); larvae of malaria vector, Anopheles subpictus, Grassi; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(40 citation statements)
references
References 79 publications
2
38
0
Order By: Relevance
“…Green synthesized zinc oxide nanoparticles were toxic to Rhipicephalus microplus and Pediculus humanus capitis and the larvae of Aedes subpictus and Culex quinquefasciatus showed LC 50 values of 29.14, 11.80, 11.14, and 12.39 mg/L, respectively [33].…”
Section: Discussionmentioning
confidence: 99%
“…Green synthesized zinc oxide nanoparticles were toxic to Rhipicephalus microplus and Pediculus humanus capitis and the larvae of Aedes subpictus and Culex quinquefasciatus showed LC 50 values of 29.14, 11.80, 11.14, and 12.39 mg/L, respectively [33].…”
Section: Discussionmentioning
confidence: 99%
“…0.1 g of zinc oxide was added to 250 ml of Erlenmeyer flasks containing deionized water followed by 1 % Pichia fermentans JA2 culture supernatant (Prasad and Jha 2009;Kirthi et al 2011). The flask was further incubated at 37°C under agitation (200 rpm) for 24-48 h.…”
Section: Microbial Synthesis Of Zno Npsmentioning
confidence: 99%
“…Acaricidal, licicidal and larvicidal activities of the synthesized ZnO nanoparticles on blood -feeding parasitesRhipicephalus (Boophilus) microplus (Canestrini, 1888), Pediculus humanus capitis (De Geer,1767), Anopheles subpictus (Grassi, 1899) and Culex quinquefasciatus (Say, 1823) revealed an increase in mortality when concentration increased; moreover, considering optimal time for lethal effects of ZnO nanoparticles after 24 hours, it was 100 % proved. In the comparison made between acaricidal, licicidal and larvicidal activities of zinc oxides and the synthesized ZnO nanoparticles, the mortality effect of ZnO nanoparticles was significant (Kirthi et al, 2011). Rouhani et al (2012) (Burckhardt and Lauterer, 1989)) and found out a greater insecticidal effect of Amitraz than the above nanoparticles.…”
Section: Figure 4: Ftir Of Synthesized Zno Nanoparticlesmentioning
confidence: 99%
“…Application of nanomaterials can revolutionize agriculture by developing potential and effective methods for pest management (Rai and Ingle, 2012). Some studies have reported the toxic effects of metal nanoparticles (such as silver, zinc, aluminum, and titanium oxide) on plants, crustaceans, bacteria, fungi, pathogens and pests (Elchiguerra et al, 2005;Goswami et al, 2010;Kairyte et al, 2013;Kirthi et al, 2011;Manzo et al, 2011;Morones et al, 2005;Reddy et al, 2007;Rouhani et al, 2012;Samuel and Guggenbichler 2004). Among them, zinc oxide (ZnO) nanoparticle is best-known compound (Mitra et al, 2012) commonly used as agricultural fungicide (Waxman 1998).…”
Section: Introductionmentioning
confidence: 99%